Adaptive pulsed-laser welding of electrical laminations - Vegelj, David (Strojniški vestnik, 2014)
In this contribution we develop and describe a new, adaptive, pulsed-laser welding method for thin electrical laminations. By using a reflectivelaser sensor and a custom-made control unit with the appropriate software the system triggers the laser pulse only at the contacts betweenthe laminations. In this way the total laser pulse energy and, consequently, the specific power losses of the electromotor, where the stack isused, are significantly reduced. This new method has great potential in the serial production of electromotors.
Keywords: lasersko varjenje; magnetne lastnosti; rotorji; statorji; varjenje lamel